Culture and theme in the translation of Brazilian Annual Reports - Siqueira, Carolina (The ESPecialist, 2012)
The new approaches to Translation Studies (Snell-Hornby, 1988) postulate that every translation problem must be analysed taking cultural issues into account. In other words, translation is no longer seen as a mere lexico-grammatical transcodification between texts. In the present paper, four Annual Reports were studied from this standpoint, focussing on an organisational element of the text that, according to Baker (1992), is language– and culture-specific: the Theme, or point-of-departure of the message (Halliday, 1994). The main hypothesis was: if the original and the translated reports were produced aiming at different audiences which, in turn, have different background knowledge, this must reflect on the translated reports in many ways – one of them is a re-configuration of the Themes when compared with the original texts, including the appearance of new Themes motivated by an attempt to adequate the text to the target culture. The results showed that the Themes of the original and of the translated texts differed mainly in grammatical terms, which can be evidencing a disregard for the cultural issue in the translation of Brazilian Annual Reports.